CHANGES IN THE LEVEL OF INTERLEUKIN-4 AND INTERLEUKIN-6 IN RESPONSE TO ANGIOPROTECTIVE THERAPY IN CHILDREN WITH SEVERE BIRTH ASPHYXIA - Danylova, Viktoriia (Medicinski časopis, 2020)
The development of clinical and laboratory criteria for diagnosis of systemic inflammatory response significantly expanded the employment of this concept in clinical practice. Correlation between the levels of anti-inflammatory and pro-inflammatory cytokines is an important aspect in regulation of the onset and development of systemic inflammatory response as its treatment is still an urgent problem in modern medicine. Treatment of systemic inflammatory response includes three main links: effect on the levels of endotoxin, cytokines and the state of endothelium. Currently there is no unified approach to the solution of this problem, which determines the relevance of the topic.The aim of the research was to study the efficacy of Deproteinized hemodialysate from the blood of veal calves in systemic inflammatory response in newborns with severe asphyxia at birth.The study involved examination of 16 newborns with severe asphyxia at birth, who received Deproteinized hemodialysate from the blood of veal calves as part of standard therapy from the first day of the disease at a dose of 0.5 ml / kg (study group),  The study implied a follow-up assessment of interleukin-4 (IL-4), interleukin-6 (IL-6) levels.  Sign test and Wilcoxon test were used for paired samples (time course of treatment); Kolmogorov-Smirnov and Mann-Whitney tests were used for non-paired samples (subgrouping by feature). To investigate the influence of the independent variable on the dependent variable we used Kruskal-Wallis and median tests as nonparametric analogs of the variance analysis.At this stage a lot of attention is paid to investigating the ways of pharmacological correction of nitrogen oxide metabolism disturbances in endothelial dysfunction. There is evidence for positive effect of various pharmacological agents on functional state of endothelium. Deproteinized hemodialysate derived from the blood of veal calves is a vasoprotector and is a combination of a number of physiologically active ingredients stimulating oxygen utilization by tissues in hypoxic conditions, enhancing glucose transport through biological membranes, intensifying intracellular adenosine triphosphate synthesis, and increasing the proportion of aerobic glycolysis.Administration of Deproteinized hemodialysate from the blood of veal calves in the treatment of systemic inflammatory response in newborns with severe asphyxia at birth exerts influence on biochemical pattern of systemic inflammatory response by reducing inflammation and reducing synthesis of cytokines.
Keywords: newborns, asphyxia, systemic inflammatory response, cytokines, vasoprotective therapy